Comprehensive Longitudinal Surveillance of the IgG Autoantibody Repertoire in Established Systemic Lupus Erythematosus. Issue 5 (24th March 2019) - Vordenbäumen, Stefan; Brinks, Ralph; Hoyer, Annika; Fischer‐Betz, Rebecca; Pongratz, Georg; Lowin, Torsten; Zucht, Hans‐Dieter; Budde, Petra; Bleck, Ellen; Schulz‐Knappe, Peter; Schneider, Matthias
Abstract : Objective: To investigate the role of epitope spreading in established systemic lupus erythematosus (SLE). Methods: IgG autoantibody reactivity with 398 distinct recombinant proteins was measured over a period of 6 years in 69 SLE patients and compared to that in 45 controls. Changes in mean fluorescence intensity (MFI), number of autoantibodies to distinct antigens, and reactivity with distinct clones of established antigenic targets (e.g., U1 RNP, Sm, and ribosomal P) representing epitope fine mapping were assessed. Linear mixed modeling, adjusted with Bonferroni correction for age and sex, was applied. Results: The total number of autoantibodies, mean MFI, and number of autoantibodies in epitope fine mapping were higher in SLE patients compared to controls ( P < 0.0001). The total number of antibodies to distinct autoantigens remained stable over time, while the mean MFI decreased over time in SLE ( P < 0.021). SLE patients showed variable recognition of epitopes in fine mapping over time. In particular, in SLE patients, more clones of the U1 RNP complex were recognized at the time of new organ involvement (+0.65) ( P = 0.007). Mean MFI was higher in patients with lupus nephritis ( P = 0.047). The time‐averaged MFIs of 22 individual autoantibodies (including double‐stranded DNA [dsDNA]) were higher, after Bonferroni correction, in SLE ( P < 0.0001). The MFIs of dsDNA and histone cluster 2 H3c were associated with scores on the Systemic Lupus Activity Measure ( P < 0.0001). Conclusion: Longitudinal surveillance of the IgG autoantibody repertoire in established SLE reveals evidence of sustained breadth of autoantibody repertoire without significant expansion. Associations of disease activity with dsDNA and with histone H3 autoantibodies were confirmed.